Predictors of risks from obesity that impact poor prognosis in patients infected with Sars-CoV-2 (Research, Society and Development, 2020)
Coronavirus 2019 is considered a morbidity transmitted by the positive-chain RNA SARS-CoV-2 virus, which causes deleterious effects to the respiratory system and can trigger from mild to fatal symptoms. Parallel to the current pandemic crisis is obesity, another pandemic, characterized as an accumulation of dysfunctional adipose tissue that is generally correlated with low inflammation systemic status. Thus, the objective of the study was to carry out an integrative literature review in order to investigate the risk factors related to obesity that reverberate for the poor prognosis of obese patients infected with Sars-Cov-2. The methodology was based on the analysis of articles taken from PUBMED, in the English language that dealt with the theme, whose search was made using the descriptors: obesity, covid-19 and risk factors to identify articles published in 2020. The Recent findings elucidate a negative association in obese individuals admitted with SARS-CoV-2, especially with regard to the immune response, a marked risk for the development of ARDS, since both share common metabolic and inflammatory pathways, which reverberate to exacerbation of the disease. Thus, in order to avoid progression and reduce the serious results of COVID-19, it is necessary to monitor and manage more ephemerally and judiciously this public by health professionals, in addition, it is pertinent to adopt measures based on healthy lifestyle to improve both nutritional status, as well as systemic markers of immune functions in this pandemic period.